Premarital Guidance and The Formation of Sakinah Families In the Family Psychology Perspective - Nanang Nur Hidayat; Rohmah Maulidia; Umi Rohmah (Institut Agama Islam Negeri Ponorogo, 2026)
Background/Introduction: The high divorce rate in Ponorogo during 2022–2023 indicates the importance of strengthening premarital guidance programs for prospective brides and grooms. However, premarital guidance is still often perceived merely as an administrative formality, so its effectiveness in establishing sakinah families requires deeper examination. Research Objectives: This study aims to describe the practice of premarital guidance, analyze the legal effectiveness of its implementation, and identify the family psychological impacts of premarital guidance for prospective brides and grooms at the Office of Religious Affairs (KUA) of Jenangan District, Ponorogo. Methodology: This study employed a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana model through the stages of data collection, data condensation, data display, and conclusion drawing. Results: The findings reveal that premarital guidance at the Jenangan KUA is conducted independently based on the Regulation of the Director General of Islamic Community Guidance Number 172 of 2022. The legal effectiveness of the program has not been fully optimal because it has not fulfilled all indicators of legal effectiveness according to Soerjono Soekanto. In addition, the psychological impact of premarital guidance on prospective couples has not yet provided a fully significant influence in realizing sakinah families. Unique Contribution: This study integrates the perspectives of family psychology and legal effectiveness in examining the practice of premarital guidance within the KUA environment. Conclusion: Premarital guidance plays an important role in establishing sakinah families, yet its implementation still needs improvement to become more effective and substantive. Recommendations: Future studies are recommended to examine the effectiveness of premarital guidance in various KUA regions using broader approaches.